Are single plane intraoperative and biplanar postoperative radiographic measurements of acetabular cup position the same?. Issue 5 (September 2020) - Harold, Ryan E; Delagrammaticas, Dimitri; Keller, Tyler; Butler, Bennet; Stover, Michael D; Manning, David W
Purpose: Supine positioning and the use of fluoroscopy during direct anterior approach total hip arthroplasty (DAA THA) have been reported to improve acetabular component positioning. This study aims to compare 2-dimensional intraoperative radiographic RadLink measurements of acetabular component position with 3-dimensional postoperative 3D SterEOS measurements. Methods: Intraoperative fluoroscopy and RadLink (El Segundo, CA, USA) were used to measure acetabular cup position intraoperatively in 48 consecutive patients undergoing DAA THA. Cup position was measured on 6-week postoperative standing EOS images using 3D SterEOS software (EOS Imaging, SA, Paris, France) and compared to RadLink findings using Student's t-test. Safe-zone outliers were identified. We evaluated for measurement difference of > +/– 5°. Results: RadLink acetabular cup abduction measurement (mean 43.0°) was not significantly different than 3D SterEOS in the anatomic plane (mean 42.6°, p = 0.50) or in the functional plane (mean 42.7°, p = 0.61). RadLink acetabular cup anteversion measurement (mean 17.9°) was significantly different than 3D SterEOS in both the anatomic plane (mean 20.6°, p = 0.022) and the functional plane (mean 21.2°, p = 0.002). RadLink identified 2 cups outside of the safe-zone. However, SterEOS identified 12 (anatomic plane) and 10 (functional plane) outside of the safe-zone. In the functional plane, 58% of anteversion and 92% of abduction RadLink measurements were within +/– 5° of 3D SterEOS. Conclusions: Intraoperative fluoroscopic RadLink acetabular anteversion measurements are significantly different than 3D SterEOS measurements, while abduction measurements are similar. Significantly more acetabular cups were noted to be outside of the safe-zone when evaluated with 3D SterEOS versus RadLink.